Description of breast cancer patients at Hasan Sadikin hospital Bandung based on age and stadium - Lokarjana, Lukmana; Hamidah Abbas, Endah; Aida Fathya, Nurul; Wahyuni Kartika, Ajeng (ACTA Medical Health Sciences, 2023)
Breast cancer is a disease when normal cells are genetically mutated and become abnormal. Cells can divide and proliferate abnormally and invade breast tissue originating from the ductal epithelium or its lobules. Malignant disease caused by breast cancer is a significant problem faced by women around the world. In 2017, breast cancer experienced by women ranked firstin new cases, namely 252,710 cases. Every increase in age is thought to be one factor influencing breast cancer incidence due to long-term hormonal exposure. The study’s objective was to describe the age and stage levels of the patients with breast cancer at Hasan Sadikin Hospital Bandung, employing descriptive method. The collected data was obtained from the medical records of breast cancer patients recorded between January to December 2018 at the Surgical Oncology Unit of Hasan Sadikin Hospital Bandung. Sampling was carried out using a total sampling technique. The results showed there were 414 patients with breast carcinoma. Breast cancer was primarily found at the age of 36-50 years in 52.7% of cases. The most prevalent stage of breast cancer is stage III B, with 41.1%. Breast cancer incidence increases with age, and the high proportion in stage III is due to the lack of information and awarenessabout early detection and a delay in seeking treatment. In order to reduce the number of breast cancer cases, it is recommended that related regional health installations/facilities provide further education and information regarding the dangers of breast cancer for women. DOI : 10.35990/amhs.v2n1.p1-8 REFERENCE Kementerian Kesehatan RI. (2015). Pusat Data dan Informasi Kesehatan: Stop Karsinoma. Infodatin-Karsinoma, 1–82. Hall, J. E., & Guyton, A. C. (2014). Guyton dan Hall Buku Ajar Fisiologi Kedokteran (edisi ke-12). Laktasi. Elsevier, Singapore, hlm. 973–978. Mescher, L. A. (2011). Histologi Dasar Janqueira: Teks dan Atlas (edisi ke-12). Kelenjar Payudara. McGraw Hill Medical, hlm. 396–402. American Cancer Society. (2017). Cancer Facts and Figures 2017. Genes & Development, 21, 2525–2538. GLOBOCAN & International Agency for Research on Cancer (IARC). (2012). Estimated Cancer Incidence, Mortality and Prevalence Worldwide in 2012. Tersedia di: http://globocan.iarc.fr/Pages/fact_sheets_cancer.aspx [Diakses 23 Desember 2021]. Humaera, R., & Mustofa, S. (2017). Diagnosis dan Penatalaksanaan Karsinoma Mammae Stadium 2. Jurnal Kedokteran Fakultas Kedokteran Lampung, 7(April), 103–107. Pusat Data dan Informasi. (2016). InfoDatin Bulan Peduli Karsinoma Mammae. Kementerian Kesehatan Republik Indonesia, 1–68. Sander, M. A. (2011). Profil Penderita Karsinoma Mammae Stadium Lanjut di RS Hasan Sadikin Bandung. Jurnal Farmasains, 1, 1–93. Faida, E. W. (2016). Analisa Pengaruh Faktor Usia, Status Pernikahan dan Riwayat Keluarga terhadap Pasien Karsinoma Mammae di RS Onkologi Surabaya. Jurnal Ilmiah, 2(1), 1–7. Dewi, G. A. T., & Hendrati, L. Y. (2015). Analisis Risiko Karsinoma Mammae Berdasarkan Riwayat Pemakaian Kontrasepsi Hormonal dan Usia Menarche. Jurnal Berkala Epidemiologi, 3(1), 12–23. Agustini, D. D., Surahman, E., & Abdulah, R. (2015). Quality of Life Patients with Breast Cancer Therapy: Combination Fluorouracil, Doxorubicin, and Cyclophosphamide. Indonesian Journal of Clinical Pharmacy, 4(3), 175–185. Rahayuwati, L., Ibrahim, K., & Komariah, M. (2017). Pilihan Pengobatan Pasien Karsinoma Mammae Masa Kemoterapi: Studi Kasus. Jurnal Keperawatan Indonesia, 20(2), 118. Desanti, O. I., Sunarsih, I., & Supriyati. (2010). Persepsi Wanita Berisiko Karsinoma Mammae tentang Pemeriksaan Payudara Sendiri di Kota Semarang. Berkala Kedokteran Masyarakat, 26(3), 152–161. Indrati, R. (2018). Faktor-Faktor Risiko yang Berpengaruh Terhadap Kejadian Karsinoma Mammae Wanita. Kementerian Kesehatan RI. Sutrisno, E., Purnama, P., & Muthmainah, S. (2016). Evaluasi Kepatuhan Pasien Karsinoma Mammae dalam Mengikuti Siklus Pengobatan Terapi di Salah Satu RS Pemerintah Bandung. Prosiding Rakernas & Pertemuan Ilmiah Ikatan Apoteker Indonesia, hlm. 79–82. Siahaan, E. R. (2011). Prevalensi Karsinoma Mammae di RS Hasan Sadikin Bandung Periode Januari–Desember 2009. Skripsi, Universitas Kristen Maranatha. Ghoncheh, M. (2016). Incidence and Mortality and Epidemiology of Breast Cancer in the World. Asian Pacific Journal of Cancer Prevention, 17(Special Issue), Cancer Control in Western Asia. Akbar, A. (2016). Hubungan Usia Terhadap Derajat Diferensiasi Karsinoma Mammae pada Wanita. Jurnal Kedokteran Diponegoro, 5, 327–361. Rahayu, S. A., dkk. (2017). Hubungan Usia dan Paritas dengan Kejadian Karsinoma Mammae di RSUD Dr. H. Abdul Moeloek, Bandar Lampung. Dian, I. M. (2012). Karsinoma Mammae pada Wanita Usia Muda di RSUP Sanglah Denpasar Tahun 2002–2012. Diahpradnya, P., dkk. (2016). Karakteristik Karsinoma Mammae Usia Muda di RSUP Sanglah, 2014–2016. hlm. 76–92. Chen, H. L. (2016). Effect of Age on Breast Cancer Patient Prognoses: A Population-Based Study Using the SEER 18 Database. University School of Medicine, Hangzhou, China. Rosai, J. (2011). Rosai and Ackerman's Surgical Pathology (edisi ke-10, Vol. 2). Breast. Elsevier Sanders, hlm. 1659. Maru, D., dkk. (2005). HER-2/neu and p53 Overexpression as Biomarkers of Breast Carcinoma in Women Age 30 Years and Younger. American Cancer Society. Pandina, N. (2018). Kesehatan Perempuan: Ketahui Faktor Penentu untuk Hidup Berkualitas. Majalah Life, Love, and Laughter, 3(2). National Cancer Institute. (2013). Surveillance, Epidemiology, and End Results Program: Stat Fact Sheet - Female Breast Cancer. Tersedia di: http://seer.cancer.gov/statfacts/html/breast.html [Diakses 2 September 2021]. Adrian, K. (2021). Benarkah Usia Memengaruhi Kesuburan Wanita? Ini Faktanya. Tersedia di: https://www.alodokter.com/benarkah-usia-memengaruhi-kesuburan-wanita-ini-faktanya [Diakses 2 September 2021]. Smeltzer, S. C., & Bare, B. G. (2013). Brunner dan Suddarth: Buku Ajar Keperawatan Medikal Bedah (Edisi 12, Volume 2). Jakarta: EGC. Kalli, S., Semine, A., Cohen, S., Naber, S. P., Makim, S. S., & Bahl, M. (2018). American Joint Committee on Cancer’s Staging System for Breast Cancer, Eighth Edition: What the Radiologist Needs to Know. Radiological Society of North America, hlm. 1923–1927. Arsittasari, T. (2016). Faktor-Faktor yang Berhubungan dengan Kejadian Karsinoma Mammae di RSUD Kota Yogyakarta. Yogyakarta: Poliklinik Kesehatan Yogyakarta. Margaretha, S. S. (2018). Karakteristik Penderita Karsinoma Mammae di RSUP Haji Adam Malik Tahun 2014–2016. Medan: Fakultas Kedokteran Universitas Sumatra Utara. Dyanti, G. A. R. (2016). Faktor-Faktor yang Berhubungan dengan Keterlambatan Penderita Karsinoma Mammae dalam Melakukan Pemeriksaan Awal ke Pelayanan Kesehatan. Jurnal Kesehatan Masyarakat, 11(2). Denpasar: Universitas Udayana.